An evaluation of the impact of rcog guidance on the recognition of severe perineal trauma. (18th April 2012) - McClean, S; Farrar, D; Tuffnell, D
Abstract : Background: In 2007 the Royal College of Obstetricians and Gynaecologists (RCOG) recommended that women with genital tract trauma sustained during vaginal birth should undergo a systematic assessment including a rectal examination to assess the severity of damage prior to suturing. Objectives: To evaluate the impact of RCOG guidance on the proportion of women receiving a systematic examination prior to suturing of genital tract trauma and assess the proportion of severe perineal trauma identified. Methods: A random sample of obstetric records were reviewed for the three years before (2004-2006) and following College guidance (2008-2010) to determine the proportion of women with second degree tears who had undergone a pre-repair systematic examination. Prospectively collected data on all third and fourth degree tears were examined within the study years. Results: From 2004 to 2006, 3% of women had documented evidence of a pre-repair systematic assessment, this increased to 33% between 2008 and 2010. Third degree tears were identified in 1% (189/13, 880) of women between 2004 and 2006 and 2% (345/14, 654) between 2008 and 2010. The rate of fourth degree tears was unchanged (0.1%). Conclusions: RCOG guidance on pre-repair examination led to an increase in the proportion of women undergoing a pre-repair systematic assessment including rectal examination, this was associated with doubling of the proportion of severe perineal trauma identified. Work to increase the rate of documented pre-repair systematic examination may increase the identification of severe trauma further.